The Work of David Gottlieb: A Success Story (Communications in Computational Physics, 2011)
This article is a brief survey of David Gottlieb's extraordinary research career.It is impossible to give a thorough presentation of all his research and the impactof his work, but we shall describe the main contributions and give examples of theresults in some of his papers. David was for many years the dominating person in thedevelopment of spectral methods, and we devote much of the space in this article tothis field.